Evaluation of land suitability for Coffee (Coffea sp.) in Nawangan District, Pacitan Regency, East Java. Issue 1 (1st February 2022) - Rahmatika, D E; Supriyadi,; Herawati, A; Widijanto, H; Nufus, M; Masyithoh, G
Abstract: Nawangan District has been hit by clove crop failures for years. Due to this incident, alternative plant replacements are needed following the land conditions in the area. Coffee ( Coffea sp. ) is one of the relevant choices. Land evaluation needs to be done to determine the land suitability class. This study aims to determine the land suitability class of coffee plants in Nawangan District. The type of coffee used in this research is Coffea arabica and Coffea canephora . This study uses the matching method with the minimum law on each land unit. Based on data obtained from field surveys and laboratory analysis, the actual land suitability for the two types of coffee is S3 (marginal), with various limiting factors. Coffea arabica has a limiting factor: temperature, water availability, rooting condition, oxygen availability, nutrient retention, and nutrient availability. The limiting factors of Coffea canephora are rooting condition, oxygen availability, nutrient retention, and nutrient availability. The improvement to decrease the limiting factors are irrigation, liming, composting, fertilizing, and adding organic matter. The potential land suitability class for Coffea arabica after improvement efforts was S3, while for Coffea canephora was S2 and S3. So based on the smallest limiting factor, the appropriate type of coffee in Nawangan District is Coffea canephora.